Diversity of bioactive secondary metabolites produced by medicinal plants of Physalis angulata L. (Ciplukan). Issue 1 (May 2021) - Mastuti, R; Rosyidah, M
Abstract: Plants are a main source of various types of secondary compounds. Plant secondary compounds play a greater role in interacting with the environment than contributing to the growth and development. Therefore, different environmental conditions besides influencing growth can also affect the profile and concentration of secondary compounds. Ciplukan ( Physalis angulata L.) has been known as medicinal plants. The medicinal properties are derived from bioactive secondary compounds especially withanolide and physalin. This study aims to identify the diversity of secondary metabolites found in in vitro callus and plants tissue of ciplukan. Withanolide and physalin profiles of callus tissues, cotyledonary shoot-derived plantlet and germinated seeds-derived plant, were evaluated by LC-MS analysis. The LC-MS analysis of methanol extract showed the diversity in the amount and type of withanolide and physalins. This study confirmed that in undifferentiated callus cultures and in vitro induced plantlet of P. angulata the biosynthesis activity was not altered and the accumulation sites of withanolides were not missing. However in vitro regenerated plant produced withanolides and physalins in higher number. Therefore, modification of plant cell culture system to improve withanolide including physalin production of P. angulata is a good future prospect.